(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Age-related macular degeneration (AMD) is a frequent cause of irreversible blindness in persons of advanced age and possesses high prevalence and propensity to progressing. Material and methods. Disturbances of clinical indices in 108 patients with the dry form of age-related macula degenerations was investigated. Results. Visual acuity in patients of the basic group was 0.53+0.06 that was lower (p<0.01) than indices of the control group (0.05). Total field of vision was (518.0+0.3) degrees that was lower (p<0.01) than indices of the control group. There was reduction of the level of CFFF up to (34.7+0.2) Hz that was lower (p<0.05) than the indices of the control group, the level TES by PH has made (96.6+0.2) mcA that was higher (p<0.05) in comparison with indices of the control group, there was reduction in the level of CFFD by PH up to (37.8+0.2) Hz that was lower (p<0.05) in comparison with indices of the control group. Lengthening of the time of restoration of visual acuity after photostress — test was noted up to (63.3+0.5) s that exceeded (p<0.01) indices of the control group. Conclusion. There was established reduction (p<0.01) of visual acuity, total field of vision, reduction in the level of CFFF, increase in the level of TES by PH and reduction of CFFD by PH in comparison with indices of the control group (p<0.01), as well as lengthening of the time of restoration of visual acuity by carrying out photostress -test.